2023
DOI: 10.1007/s10570-023-05317-2
|View full text |Cite
|
Sign up to set email alerts
|

Superabsorbent fabric: in situ polymerisation of macroporous starch–sodium alginate–polyacrylate hydrogel on fibre surface

Abstract: Super-absorbent fabric provide a comfortable microenvironment for personal protective equipment. We prepared a super-absorbent and strong water retention fabric by in situ polymerization of starch-sodium alginate-polyacrylate (St-SA-PAA) hydrogel on the surface of polyester fabric. The pore size distribution of gel on fabric was 30~91 μm. Bene ting from the capillarity of polyester ber, the water absorption rate of St-SA-PAA gel could be increased from 2.8 to 10 g/min, when it was deposited on fabric. The wate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In the infrared spectra of AA and MAA, 1701 and 1697 cm –1 are CO stretching vibrations, 1636 cm –1 is a CC characteristic absorption peak, and 1045 cm –1 is a C–OH group vibration . The reaction of CMC with AA–MAA before and after heating in a water bath (Figure b) showed that the characteristic absorption and torsion peaks of CC at 1636 and 819 cm –1 were weakened by heating and the stretching vibration of C–OH was weakened, indicating that C–OH grafted CC . After cross-linking with IP6, the characteristic absorption peaks of CC disappeared.…”
Section: Resultsmentioning
confidence: 99%
“…In the infrared spectra of AA and MAA, 1701 and 1697 cm –1 are CO stretching vibrations, 1636 cm –1 is a CC characteristic absorption peak, and 1045 cm –1 is a C–OH group vibration . The reaction of CMC with AA–MAA before and after heating in a water bath (Figure b) showed that the characteristic absorption and torsion peaks of CC at 1636 and 819 cm –1 were weakened by heating and the stretching vibration of C–OH was weakened, indicating that C–OH grafted CC . After cross-linking with IP6, the characteristic absorption peaks of CC disappeared.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, natural polymers, especially polysaccharide-based superabsorbent polymers, have garnered significant attention due to their non-toxicity and good hydrophilicity, biocompatibility, and biodegradability compared with synthetic polymers. The main materials used for superabsorbent polymers are natural polymers, such as cellulose [ 48 , 49 , 50 , 89 ], chitosan [ 51 , 52 , 53 , 90 ], starch [ 54 , 55 , 56 , 57 , 91 ], proteins [ 9 , 58 , 59 , 60 ], amino acids [ 61 , 62 , 63 , 92 ], and alginate [ 64 , 65 , 66 , 93 ].…”
Section: Superabsorbent Polymersmentioning
confidence: 99%
“…ity, biocompatibility, and biodegradability compared with synthetic polymers. The main materials used for superabsorbent polymers are natural polymers, such as cellulose [48][49][50]89], chitosan [51][52][53]90], starch [54][55][56][57]91], proteins [9,[58][59][60], amino acids [61][62][63]92], and alginate [64][65][66]93].…”
Section: Common Natural Polymersmentioning
confidence: 99%